Predictive Model of Burnout and Labor Satisfaction - Portillo, Dra. María Teresa Escobedo; Gómez, Dr. Andrés Hernández; Valerio, Dr. Jesús Gonzalo Palacios; López, Dr. Roberto Romero (RA Journal of Applied Research, 2018)
The purpose of this study was to determine the relationship between burnout syndrome and job satisfaction in full-time professors of a Mexican university. The sample consisted of 230 randomly selected teachers, of whom 139 men and 76 women. The design of the study was, not experimental, transversal, quantitative, descriptive, and exploratory. To measure the prevalence of burnout syndrome, it was taken as reference the SBS-HP, to measure job satisfaction was taken Scale of Work Satisfaction based on Socio-cultural and Ergo-environmental factors for teachers of HEI in Mexico.A model of structural equations was performed according to the method of optimizing Partial Least Squares (PLS) in SmartPLS software. As a result it was found that there is a weak negative relation between job satisfaction and burnout syndrome (path coefficient -0296), that is, the greater satisfaction of the teachers, the lower risk of developing burnout.